Linguistics and the Teaching of English - Marckwardt, Albert H. (Indiana University Press, 2022)
For many years teachers of English felt that linguistics had little to do with their day-to-day classroom activities. More recently, during a period of change which affected the teaching of many subjects, the attitude toward linguistics underwent a sudden and sharp reversal. Linguistic methods of English teaching became a common topic of formal and informal discussion. Today there is a real danger that the profession may be expecting too much from linguistics. In this volume Mr. Marckwardt presents a cool, realistic analysis of the possible applications of linguistics to English teaching at all levels of instruction. He deals first with the direct application of linguistics to the teaching of grammar and to thorny questions of usage. Next, he considers the areas where the use of linguistics is partial or indirect: composition, spelling, reading, and literature. Finally, because he believes that all teaching must be conducted in terms of a broad educational philosophy, the author includes a discussion of the place of language study in the curriculum.